Once were teachers? Australian teacher education policy and shifting boundaries for teacher educators. Issue 4 (8th August 2019) - White, Simone
ABSTRACT: Teacher educators are an increasingly diverse, occupational group due to the marketization of teacher education. Global policy reforms mean that educating teachers now occur in a myriad of ways, across multiple learning sites. In the Australian context, recent initial teacher education reforms mean that classroom teachers are required to take greater responsibility for teacher preparation, while university-based teacher educators are required to maintain school–university partnerships and show evidence of the impact of their programs on the graduates they produce. These changes herald significant changes for cross-sectoral collaboration and the emergence of 'hybrid' teacher educators who need to work across and between the boundaries of schools, their communities and universities. Drawing from a partnership study, this paper provides insights into the professional learning and boundary spanning of two mentor teachers as they navigated changes in their dualistic identities, roles and places of work as both teachers and school-based teacher educators.